1978
DOI: 10.1108/eb002307
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Instruments in International Training

Abstract: Confronted with cross‐cultural training the authors have used data collection instruments for flexibility and adaptability and to bridge the cultural and language gap. The frame of reference here is international but many of the advantages might also apply in other training contexts. This is how the utilisation reported in this article occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, a study comparing the relative importance of ten work values in the United States, Australia, Canada, and Singapore found similarities among the countries (Popp, Davis, and Herbert, 1986). A similar study comparing managers in the United States, Colombia, Peru, and Chile also found that the countries shared similar work values (Peters and Lippitt, 1978). The results of these two studies show that good pay, opportunity for growth, and a feeling that the job is important are universally valued.…”
Section: Measuring Managerial Valuesmentioning
confidence: 76%
“…For example, a study comparing the relative importance of ten work values in the United States, Australia, Canada, and Singapore found similarities among the countries (Popp, Davis, and Herbert, 1986). A similar study comparing managers in the United States, Colombia, Peru, and Chile also found that the countries shared similar work values (Peters and Lippitt, 1978). The results of these two studies show that good pay, opportunity for growth, and a feeling that the job is important are universally valued.…”
Section: Measuring Managerial Valuesmentioning
confidence: 76%
“…The scale used in this study is a potentially useful springboard for a broader discussion of cross-cultural differences and their impact on career development and career counselling practices. Peters and Lippitt (1978) noted that motivation instruments, translated for a particular culture, might have many advantages, such as (a) increase of peoples involvement in the learning/action process; (b) efficiency of administration and economic value, in comparison with the utilisation of consultants or lengthy interviews; (c) variety of utilisation instruments can be used to provide a trend that can be diagnostic; availability of immediate fe-edback; raise awareness about assumptions, feelings or beliefs; educate; offer direction and serve as an stimulus for corrective action; and (d) a degree of objectivity and opportunity for comparison between individuals.…”
Section: Implications For Human Resource Development Practices Potential Uses Of the Instrumentmentioning
confidence: 99%